Otherness in Communication Research
XVII, 288 p. 15 illus., 12 illus. in color.
Keywords: This book offers various perspectives from media studies, interpersonal communication, and intercultural communication on the experience and effects of being othered, excluded, and treated as less than. Its three sections cover: 1) expressions of otherness in everyday life, 2) experiences of otherness in media discourses and 3) strategies against otherness in social interaction. This book challenges the expression of otherness that is frequently related on texts of colonialism and of western social hegemonic characteristic of the Global North, therefore giving voice to perspectives from the Global South, in a pluralistic reading. The collection of contexts in which the expression of otherness is highlighted in this book, are presented in the perspective of the powerless other. As a receiver involved in a communicative process, the othered individual is approached in relation to his identitarian demonstrations, both in daily life, face-to-face and virtual contexts and in critical situations. These range from households to school and to media environments, therefore enhancing a thorough perspective on the phenomenon of othering in plural contexts. Luísa Magalhães, co-editor of the Palgrave Studies in Otherness and Communication book series, is a researcher at the Centre for Philosophical and Humanistic Studies (CEFH) and Professor in Communication Sciences at the Catholic University of Portugal.